2011
DOI: 10.1051/0004-6361/201014389
|View full text |Cite
|
Sign up to set email alerts
|

Budget of energetic electrons during solar flares in the framework of magnetic reconnection

Abstract: Context. Among other things, solar flares are accompanied by the production of energetic electrons as seen in the nonthermal radio and X-ray radiation of the Sun. Observations of the RHESSI satellite show that 10 32 −10 36 nonthermal electrons are produced per second during flares. They are related to an energy flux in the range 10 18 −10 22 W. These electrons play an important role, since they carry a substantial part of the energy released during a flare. Aims. In which way so many electrons are accelerated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…The role of small scale structures due to turbulence of the CS in particle acceleration has recently studied by Nishizuka and Shibata (2013) who found that the interaction of these structures provides an approach to Fermi acceleration for particles. Mann and Warmuth (2011) pointed out that, in a medium class flare, if about 8 % of the all electrons brought into CS by reconnection inflow are accelerated, they are able to bring about 12 % of the total released energy into the flare region; in a major flare, on the other hand, up 60 % total inflow electrons need to be accelerated to the energy > 20 keV to account for 60 % the total released energy observed in the flare region. In both cases, they found that the slow-mode shock plays a role in heating and the termination shock plays a role in particle accelerations.…”
Section: Discussionmentioning
confidence: 99%
“…The role of small scale structures due to turbulence of the CS in particle acceleration has recently studied by Nishizuka and Shibata (2013) who found that the interaction of these structures provides an approach to Fermi acceleration for particles. Mann and Warmuth (2011) pointed out that, in a medium class flare, if about 8 % of the all electrons brought into CS by reconnection inflow are accelerated, they are able to bring about 12 % of the total released energy into the flare region; in a major flare, on the other hand, up 60 % total inflow electrons need to be accelerated to the energy > 20 keV to account for 60 % the total released energy observed in the flare region. In both cases, they found that the slow-mode shock plays a role in heating and the termination shock plays a role in particle accelerations.…”
Section: Discussionmentioning
confidence: 99%
“…Saint-Hilaire and Benz, 2005;Mann and Warmuth, 2011;Ryan et al, 2012). 7 This implies that coronal waves represent a non-negligible fraction of the energy released in a solar eruptive event (at least in smaller events).…”
Section: Energeticsmentioning
confidence: 99%
“…Many of these flares have already been used for comparison with the results of a shock-drift acceleration model (Mann et al 2009;Warmuth et al 2009b), and for the study of nonthermal energetics in the framework of magnetic reconnection (Mann & Warmuth 2011). Four different imaging methods were employed: CLEAN 3 , Pixon (Metcalf et al 1996), Visibiliy Forward Fit (Hurford et al 2005), and MEM_NJIT (Schmahl et al 2007).…”
Section: Observationsmentioning
confidence: 99%